Policy Implementation of Tour Guides License in Maintaining the Quality of Tourism in Bali Province - Pratiwi, Kadek Rianita Indah; Saleh, Choirul; Sentanu, I Gede Eko Putra Sri (Graduate School, Universitas Brawijaya, 2019)
Bali Regional Government intervenes tour guides profession by implementing the licensing policy. This phenomenon is associated with the increasing number of tourist visits to Bali and the important role of tour guides in maintaining tourism quality. This research aimed to analyze the implementation of the licensing policy for tour guides in Bali. Practically, this research can provide an understanding of policy implementers to pay attention to aspects of implementation in tour guide licensing policies in Bali. Then academically, this research can be a reference for tourism policy research related to implementation theory. A qualitative approach with the case-study analysis applied to this study. The research conducted semi-structured interviews, observations, and documentation studies in gaining insights from research data. In this research, we found that licensing policy for tour guides in the process of implementation found deficiencies in aspects of policy objectives and standards, policy resources, communication, socio-economic and political environments, and characteristics and disposition implementers. Keywords: License, Policy Implementation, Tour Guides.